Examining the Effect of Freezing Temperatures on the Survival Rate of Micro-Encapsulated Probiotic Lactobacillus acidophilus LA5 Using the Flash Freeze-Drying (FFD) Strategy - Elsa Acosta-Piantini; Maria Carmen Villarán; Ángel Martínez; José Ignacio Lombraña (Microorganisms, 2024)
This work proposes a novel drying method suitable for probiotic bacteria, called flash freeze-drying (FFD), which consists of a cyclic variation in pressure (up-down) in a very short time and is applied during primary drying. The effects of three FFD temperatures (−25 °C, −15 °C, and −3 °C) on the bacterial survival and water activity of Lactobacillus acidophilus LA5 (LA), previously microencapsulated with calcium alginate and chitosan, were evaluated. The total process time was 900 min, which is 68.75% less than the usual freeze-drying (FD) time of 2880 min. After FFD, LA treated at −25 °C reached a cell viability of 89.94%, which is 2.74% higher than that obtained by FD, as well as a water activity of 0.0522, which is 55% significantly lower than that observed using FD. Likewise, this freezing temperature showed 64.72% cell viability at the end of storage (28 days/20 °C/34% relative humidity). With the experimental data, a useful mathematical model was developed to obtain the optimal FFD operating parameters to achieve the target water content in the final drying.